2013
DOI: 10.3390/ijms14047480
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Receptor for Advanced Glycation End-Product (sRAGE)/Pentosidine Ratio: A Potential Risk Factor Determinant for Type 2 Diabetic Retinopathy

Abstract: This study aims to investigate potential diabetic retinopathy (DR) risk factors by evaluating the circulating levels of pentosidine, soluble receptor for advanced glycation end-product (sRAGE), advanced oxidation protein product (AOPP) as well as glutathione peroxidase (GPx) and superoxide dismutase (SOD) activities in DR patients. A total of 235 healthy controls, 171 type 2 diabetic without retinopathy (DNR) and 200 diabetic retinopathy (DR) patients were recruited. Plasma was extracted for the estimation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Recent work suggests that sRAGE/pentosidine ratio could be a risk factor determinant for DR (Ng et al, 2013 ). This study recruited 606 subjects (171 NDR, 125 with NPDR, 75 with PDR, and 235 healthy controls).…”
Section: Markers Of Diabetic Retinopathymentioning
confidence: 99%
“…Recent work suggests that sRAGE/pentosidine ratio could be a risk factor determinant for DR (Ng et al, 2013 ). This study recruited 606 subjects (171 NDR, 125 with NPDR, 75 with PDR, and 235 healthy controls).…”
Section: Markers Of Diabetic Retinopathymentioning
confidence: 99%
“…Soluble RAGE blood levels are low in patients with diabetic complications in comparison with diabetic patients without complications and nondiabetic subjects [ 37 ]. By contrast, increased levels of this receptor in patients with PDR compared with those with NPDR or without DR have also been reported [ 47 , 48 ].…”
Section: Advanced Glycation End Productsmentioning
confidence: 99%
“…There is substantial evidences to support the involvement of oxidative stress in irreversible cellular damage found in diabetes mellitus (Ng, Kuppusamy, Iqbal, & Chua, ; Ng, Chua, Iqbal, & Kuppusamy, ; Ng, Chua, Tajunisah, Pendek, & Kuppusamy, ). Previous studies showed that treatment with dietary antioxidants ameliorates diabetes mellitus and its complications (Montonen, Knekt, Järvinen, & Reunanen, ).…”
Section: Introductionmentioning
confidence: 99%